Landscape and the commercial benefits of recreation - Nico Polman; Arianne De Blaeij; Stijn Reinhard; Louis Slangen (European Regional Science Association (ERSA), 2010)
In this presentation, we will analyse whether entrepreneurial benefits depend on the landscape composition of the Dutch Ecological Main Structure (EMS) zones. The general objective of this research is to analyze economic benefits of the EMS for recreational firms. As far as we know, this research is the first empirical analysis of the link between landscape and benefits for recreational firms. To estimate the relevance of the EMS for recreational firms an indicator is developed for individual firms that gives insight in and the distance of the firm to and the size of the EMS. The total dataset consists of about 29,000 recreational firms. Analyzing accountancy data for all recreational firms was not possible given the number of organizations and their diversity. Therefore, the number of employees of a firm and the connected net added value is used as a proxy for economic benefits. The question analyzed was if the number of employees could be attributed to the EMS. The study has been carried out applying econometric analysis using location variables and firm specific variables. The results indicate that recreational firms in the neighborhood of the EMS employ relatively more people than other firms. The effect for the average firm is however limited. Most important for employment are forest areas and coastal zones. Forest areas include cultural-historic important forests, natural forests and heath areas. The coastal zones consist of tidal marshes, salt marshes and dunes. A larger distance and or combined with smaller nature areas shows a decreasing effect on the number of people employed by a recreational firm. An sequential question is whether it is possible to use the Reilly index indicator to determine ex-ante the recreational economic benefits of new developed nature areas. As a case study, we apply this indicator to a new constructed natural area in the Netherlands, a commercial wetland. Changing agricultural land use into commercial wetlands will change the use and character of landscape. The question is whether it will change the recreational benefits of recreational firms in the surroundings.
Keywords: 330